2017
DOI: 10.1016/j.jid.2017.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and the Risks of Basal Cell Carcinoma and Squamous Cell Carcinoma

Abstract: Sunlight is the principal environmental risk factor for keratinocyte cancers, but other carcinogens have also been implicated, including tobacco smoke. Findings have been conflicting, however. We investigated associations between cigarette smoking and incidence of basal cell carcinoma (BCC) or squamous cell carcinoma (SCC) in QSkin, a prospective study of skin cancer (N = 43,794). Smoking history was self-reported at baseline; newly diagnosed BCCs and SCCs were ascertained through data linkage and verified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 28 publications
(31 reference statements)
3
48
1
2
Order By: Relevance
“…In addition, there was also some evidence showing that smoking might be a risk factor for SCC rather than BCC. 32,33 Our stratified analysis by geographic region indicated that use of diuretics was significantly associated with increased risk of SCC in are required to confirm our findings.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In addition, there was also some evidence showing that smoking might be a risk factor for SCC rather than BCC. 32,33 Our stratified analysis by geographic region indicated that use of diuretics was significantly associated with increased risk of SCC in are required to confirm our findings.…”
Section: Discussionsupporting
confidence: 50%
“…Although smoking is a well‐known risk factor for many human cancers, findings regarding potential associations between smoking and KC risk remain inconsistent . The magnitude of association between diuretics and BCC was similar between studies without controlling for smoking status and studies controlling for smoking status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key question is whether the observed inverse association reflects a "protective effect" of smoking on development of melanoma, or whether there are alternative non-causal explanations. It is likely that never smokers have more medical surveillance and earlier detection of disease compared with smokers as a consequence of a generally healthier lifestyle [359]. In our dataset, a greater proportion of never smokers than ever smokers self-reported that they had undergone a skin screening examination by a doctor in the 3 years prior to enrolment (75% vs 66% respectively).…”
Section: Discussionmentioning
confidence: 96%
“…Although no cancers of the skin are currently included in this list, there is strengthening evidence that smoking is a cause of cutaneous squamous cell carcinoma (cSCC) [359]. The association between smoking and melanoma remains unclear despite considerable investigation.…”
Section: Introductionmentioning
confidence: 99%